Electrochemical Study and Determination of Homovanillic Acid, the Final Metabolite of Dopamine, Using an Unmodified Disposable Electrode - Mihaela Buleandră; Lavinia Georgiana Voica; Dana Elena Popa; Irinel Adriana Badea; Emilia Elena Iorgulescu; Mihaela Carmen Cheregi (Molecules)
This paper summarizes the main findings of a study which aimed to examine the electrochemical oxidation of homovanillic acid (HVA), the final metabolite of dopamine. A pencil graphite electrode (PGE) was used as working electrode and the measurements were performed by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The type and the composition of the graphite leads used as PGE, the pH of the supporting electrolyte, as well as the scan rates were optimized by CV. The analyte was irreversibly oxidized in Britton–Robinson buffer (BRB) solutions. The interpretation of the voltammetric signals and the correlation of the acquired information were the key to addressing the electrode process undergone by HVA at the PGE. The outcomes of the pH and scan rate studies led to the conclusion that two electrons and two protons were involved in the diffusion-controlled process. Using the PGE, a linear relationship between peak current and HVA concentration was obtained between 1.0 × 10−6 M and 5.0 × 10−5 M by DPV in BRB with pH 2.0. The detection limit of 3.84 × 10−7 M was calculated. The accuracy, the precision, and the selectivity of the quantitative method have successfully undergone evaluation. The practical application of the developed voltammetric method was checked by determining the HVA concentration in spiked plasma samples, yielding good recovery values.